Investigation of the Effect of Central Placement on Open Education System - Muhammet Recep OKUR (Anı Publishing, 2019)
This study aims to reveal the numerical change of the number of open education system students according to the central placement examination. Between 2015-2018, the numerical change of the Open Education Faculty students enrolled in the higher education system was examined in the context of central placement examination. In the study examining how the changes in the central examinations applied to the transition to higher education affect the quotas and settlement rates of the faculties of open education, number of students in higher education, number of students in open education, number of students in associate degree and bachelor's degree programs, number of students, quota and number of vacancies were investigated. Anadolu University, Atatürk University and İstanbul University, which have open education faculty, constitute the scope of the research. The distribution of the number of distance education students in 2015-2018 years in three universities in research and higher education system that rates in Turkey were also discussed. Quotas and settlement rates were examined statistically by years. It is thought that the results of the research will guide the decision makers about opening new programs in open education faculties, program quotas and legal regulations.